Adult children's characteristics and intergenerational financial transfers in urban China. (January 2016) - Zhu, Haiyan
Financial transfers between adult children and their elderly parents should be viewed as part of larger family dynamics that can also involve siblings. This is particularly likely to be the case in China, where there has been a traditional emphasis on financial support within the extended family. Using data from the 1999 'Study of Family Life in Urban China' and fixed effects models, this study examines how the characteristics of adult children and their adult siblings are associated with financial transfers between them and their elderly parents. Particular attention is given to sibling differences with regard to factors such as gender, birth order, education and financial situation. The findings revealed that in urban China the traditional gender pattern is changing, in that daughters, rather than sons, now provide more financial support to their parents. However, parents still tend to give more financial assistance to sons. Children with more education (i.e., those who received more parental investment) provided greater financial support to their parents, to repay this earlier investment. Furthermore, elderly parents redistributed resources within the extended family by receiving more financial transfers from financially better-off children and giving more financial transfers to financially worse-off children. These findings suggest that the Chinese family serves as a financial buffer, with intergenerational transfers operating as a micro-level welfare system.